2011
DOI: 10.1007/s00415-011-6302-8
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits in patients with Parkinson’s disease: assessment and clinical implications

Abstract: This study reviews empirical evidence on the association between personality traits and Parkinson's disease (PD), with a twofold aim. First, to better identify non-motor symptoms, such as affective symptoms and personality changes, that could help to define the pre-motor phase of PD; second, to better understand the neurobiological bases of personality traits, a goal that is not fully accomplished by a purely anatomical approach. A literature review was performed on studies of personality traits in PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 111 publications
(131 reference statements)
2
44
3
Order By: Relevance
“…This suggests a common underlying pathophysiology shared by drug abusers and those with behavioural addictions (Volkow, Wang et al 2008). The novelty-seeking trait commonly described in PD patients with ICBs is contrary to a previously described (albeit controversial) pre-morbid “parkinsonian personality” (Poletti and Bonuccelli 2012). These so-called “typical” non-ICB PD patients scored higher on ratings of premorbid personality traits such as harm avoidance and were less novelty seeking (Menza, Golbe et al 1993; Menza 2000).…”
Section: Risk Factors For Icbs In Pdcontrasting
confidence: 72%
“…This suggests a common underlying pathophysiology shared by drug abusers and those with behavioural addictions (Volkow, Wang et al 2008). The novelty-seeking trait commonly described in PD patients with ICBs is contrary to a previously described (albeit controversial) pre-morbid “parkinsonian personality” (Poletti and Bonuccelli 2012). These so-called “typical” non-ICB PD patients scored higher on ratings of premorbid personality traits such as harm avoidance and were less novelty seeking (Menza, Golbe et al 1993; Menza 2000).…”
Section: Risk Factors For Icbs In Pdcontrasting
confidence: 72%
“…Therefore, the investigation of non-motor symptoms, such as affective disorders, that may characterize the pre-motor phase of PD has been receiving increasing interest in recent years [26][27][28].…”
Section: Affective Status and Cognitionmentioning
confidence: 99%
“…In their review, Poletti and Bonuccelli (2012) concluded that the afflicted patients present a personality profile of low novelty seeking and high harm Correspondence and reprint requests to: Anne Schienle, University of Graz, Department of Psychology, Universitätsplatz 2 / III, A-8010 Graz, Austria. E-mail: anne.schienle@uni-graz.at avoidance.…”
Section: Introductionmentioning
confidence: 98%